2013
DOI: 10.3389/fimmu.2013.00048
|View full text |Cite
|
Sign up to set email alerts
|

A proposed role for neutrophil extracellular traps in cancer immunoediting

Abstract: Upon activation, neutrophils release fibers composed of chromatin and neutrophil proteins termed neutrophil extracellular traps (NETs). NETs trap and kill microbes, activate dendritic cells and T cells, and are implicated in autoimmune and vascular diseases. Given the growing interest in the role of neutrophils in cancer immunoediting and the diverse function of NETs, we searched for NETs release by tumor-associated neutrophils (TANs). Using pediatric Ewing sarcoma (ES) as a model, we retrospectively examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
217
0
13

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(238 citation statements)
references
References 31 publications
8
217
0
13
Order By: Relevance
“…Recently, an interesting role of NETs in tumor immunology has been proposed. 35 The existence of NETs-releasing neutrophils was found in Ewing Sarcoma and authors suggested the hypothesis regarding the role of NETs in tumor. Since NETs contains several components which are highly cytotoxic to tumor cells, 36,37 we believe that increased NETs formation from hypersegmented neutrophils could be another possible mechanism for antitumor activity of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an interesting role of NETs in tumor immunology has been proposed. 35 The existence of NETs-releasing neutrophils was found in Ewing Sarcoma and authors suggested the hypothesis regarding the role of NETs in tumor. Since NETs contains several components which are highly cytotoxic to tumor cells, 36,37 we believe that increased NETs formation from hypersegmented neutrophils could be another possible mechanism for antitumor activity of neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…1,12 The proposed mechanisms regarding antitumor activity of neutrophils are oxidative damage caused by ROS generation, antibody-dependent tumor cell lysis, and NETs formation. 1,12,35 The tumor destruction caused by ROS generation is unlikely, because hypersegmented neutrophils showed decreased ROS generation in response to PMA stimulation (Fig. 4B).…”
Section: Discussionmentioning
confidence: 99%
“…By virtue of their ability to present antigens, neutrophils may directly activate a T cell response. Neutrophils may also activate dendritic cells and T cells through release of neutrophil extracellular traps (NETs) [349,350]. On top of secreting T cell chemoattractants, neutrophil-secreted TNFα, Cathepsin G and neutrophil elastase, are able to increase T cell proliferation and cytokine production, which together enhance adaptive immune responses [350].…”
Section: Neutrophils As Tumor-antigen Presenting Cellsmentioning
confidence: 99%
“…NETs have been observed in both murine and human tumors: sarcomas, pancreatic adenocarcinoma and LLC lung carcinomas [11][12][13][14] and have been shown to promote metastasis following septicemia in mice. 15 To evaluate if the presence of PAD4/ NETs in the host affects primary tumor growth, we compared tumor progression in WT mice to PAD4-deficient mice whose neutrophils are defective in NET formation.…”
Section: Presence Of Nets Increases Lewis Lung Carcinoma (Llc) Tumormentioning
confidence: 99%